2022
DOI: 10.1002/cey2.194
|View full text |Cite
|
Sign up to set email alerts
|

Single‐atom catalysis for carbon neutrality

Abstract: Currently, more than 86% of global energy consumption is still mainly dependent on traditional fossil fuels, which causes resource scarcity and even emission of high amounts of carbon dioxide (CO 2 ), resulting in a severe "Greenhouse effect." Considering this situation, the concept of "carbon neutrality" has been put forward by 125 countries one after another. To achieve the goals of "carbon neutrality," two main strategies to reduce CO 2 emissions and develop sustainable clean energy can be adopted. Notably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 371 publications
0
69
0
Order By: Relevance
“…Up to now, enormous efforts have been made to prepare high-efficiency CO 2 RR electrocatalysts, especially SACs. 1,5,14,[66][67][68][97][98][99][100][101][102] We found that the Ni of the PtNi nanoalloy and the Zn of the ZIF-8-derived Zn 1 on nitrogen-doped carbon experienced metal interchange to produce PtZn nanocrystals and Ni single atoms at high temperature. Due to the synergistic effect of PtZn nanocrystals and Ni 1 -CN, the obtained (PtZn)n/Ni 1 -CN multisite catalysts show lower energy barriers for CO 2 protonation and CO desorption in the CO 2 RR than the reference catalyst, resulting in a greatly enhanced catalytic performance of the CO 2 RR for CO (Fig.…”
Section: Gas Molecule Electrooxidation or Electroreductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, enormous efforts have been made to prepare high-efficiency CO 2 RR electrocatalysts, especially SACs. 1,5,14,[66][67][68][97][98][99][100][101][102] We found that the Ni of the PtNi nanoalloy and the Zn of the ZIF-8-derived Zn 1 on nitrogen-doped carbon experienced metal interchange to produce PtZn nanocrystals and Ni single atoms at high temperature. Due to the synergistic effect of PtZn nanocrystals and Ni 1 -CN, the obtained (PtZn)n/Ni 1 -CN multisite catalysts show lower energy barriers for CO 2 protonation and CO desorption in the CO 2 RR than the reference catalyst, resulting in a greatly enhanced catalytic performance of the CO 2 RR for CO (Fig.…”
Section: Gas Molecule Electrooxidation or Electroreductionmentioning
confidence: 99%
“…As thermal energy is being replaced with other types of energy to overcome the activation energy barrier inherent to any chemical transformation, traditional thermal catalysis has been expanded to other types of catalysis such as electrocatalysis, [1][2][3][4][5][6][7][8][9][10][11][12] photocatalysis, 13,14 plasma catalysis, 15,16 and laser catalysis, 17 just to mention a few. This shift, especially to electrocatalysis, is driven by the interest in substituting fossil fuels (which provide heat) with alternative renewable energy sources (like electricity, solar, wind, tidal, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…[7,[52][53][54][55][56][57][58] Recently, the dual/multi-atom site catalysts also have exhibited excellent catalytic activity in energy conversion and catalysis based on synergistic effects between adjacent metal atoms. [59] Compared to SACs, the adjacent metal atoms of dual/multi-atom site catalysts can also collaborate and have a certain synergistic [62] Copyright 2022, The Authors, published by Wenzhou University and John Wiley & Sons Australia, Ltd.…”
Section: Atomic Scalementioning
confidence: 99%
“…Timeline of the single-atom catalysts (SACs) with major breakthroughs from 1925 to 2022. Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license (https:// creativecommons.org/licenses/by/4.0) [62]. Copyright 2022, The Authors, published by Wenzhou University and John Wiley & Sons Australia, Ltd.…”
mentioning
confidence: 99%
“…[ 21 , 22 , 23 ]. In these proposed electrochemical reactions, the introduction of catalysts significantly reduces the extra electric energy consumption [ 24 , 25 , 26 , 27 , 28 ]. For traditional bulk and/or nanoparticles (NPs) electrocatalysts, only a few layers of the atoms on the surfaces of the catalysts are involved in the reactions, resulting in a large percentage of the metal atoms being ineffective and wasted.…”
Section: Introductionmentioning
confidence: 99%